8x-7x-6=7-13

Simple and best practice solution for 8x-7x-6=7-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-7x-6=7-13 equation:


Simplifying
8x + -7x + -6 = 7 + -13

Reorder the terms:
-6 + 8x + -7x = 7 + -13

Combine like terms: 8x + -7x = 1x
-6 + 1x = 7 + -13

Combine like terms: 7 + -13 = -6
-6 + 1x = -6

Add '6' to each side of the equation.
-6 + 6 + 1x = -6 + 6

Combine like terms: -6 + 6 = 0
0 + 1x = -6 + 6
1x = -6 + 6

Combine like terms: -6 + 6 = 0
1x = 0

Solving
1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '1'.
x = 0

Simplifying
x = 0

See similar equations:

| 10(x+2/15)=8(x-7/3) | | 35=x+(2x-1)+(4(2x-1)+2) | | 9x-16=3x+20 | | X/2=50 | | 4x-5=3x-3 | | -5=7x+1-6x | | 35=x+(2x-1)+(14(2x-1)+2) | | 115+5x=240 | | 3.5x+5=50.50 | | -15=-6r-1-2 | | 25x+57=232 | | M^(3/4)=27 | | 15x-17+2x=-34 | | 5x+9-4x=-1 | | 5x-1=4x-4 | | 6+3a+4a=-8 | | 5x-1=4x-1 | | 3x+9-2x=5 | | 440.2908=105.5668+25.748h | | 5-2[3x-4(5-x)]=6(7-x) | | 8y+15=7y-8 | | 3x+9-2=5 | | (1-14+x)/23=15 | | 4x^2=3x-2 | | 10y+7-4y=-5+6y+22. | | 1/x^2-1 | | (3+4)+z=(4+8)+3 | | (5t-20)/(4-t) | | 1/2=(4n-6)=11 | | 6y-12=3x | | 4x-2=6t+6 | | 23=35-x |

Equations solver categories